Correlation of CD4+ levels and caspase-3 in condyloma acuminata with HIV reactive patients - Nurfaiqoh, Elok; Mawardi, Prasetyadi; Dharmawan, Nugrohoaji; Julianto, Indah; Ellistasari, Endra Yustin (MEDISAINS, 2024)
Background: Human papillomavirus is an infection that causes malignancy because of persistency and modulation of apoptotic pathways, especially caspase-3. Factors that can increase persistency, recurrency, and malignancy of HPV infection include HIV infection with low CD4 levels. There is disagreement or deep molecular understanding of the induction and modulation of apoptosis in HIV-mediated CD4+ T cell depletion, especially in CA. However, it is necessary to see how CD4+ levels can influence caspase-3, so it may open up new avenues for supporting investigation to consider the presence of malignancy or therapeutic strategies regarding CD4+ can induce apoptosis.Purpose: This study aimed to determine whether there is a correlation between CD4+ levels and caspase-3 expression in condyloma acuminata with HIV reactive patients.Methods: This is an analytic observational study with a cross-sectional design. The research was conducted at Dr. Moewardi General Hospital from August to December 2023. Nineteen patients with condyloma acuminata and HIV reactive were included in this study with a consecutive sampling technique. The expression of caspase-3 was assessed using immunohistochemical staining, looking at the percentage of stained cell nuclei and cytoplasm and CD4+ levels with flow cytometry examination—data analysis using Pearson correlation.Results: Respondents in this study were primarily men, self-employed with heterosexual orientation and genito-genital-oral sexual intercourse. The statistical analysis showed no significant relationship (p: 0.300, r: -0.251) between CD4+ levels and caspase-3 expression.Conclusions: While not statistically significant, CD4+ level is reduced in correlation with increased caspase-3 expressions.